239. EVALUATION OF SUBCARINAL LYMPH NODE DISSECTION AND METASTASIS IN TRANSMEDIASTINAL RADICAL ESOPHAGECTOMY. (24th September 2022) - Shibamoto, Jun; Fujiwara, Hitoshi; Konishi, Hirotaka; Shiozaki, Atsushi; Ohashi, Takuma; Kubota, Takeshi; Shimizu, Hiroki; Arita, Tomohiro; Yamamoto, Yusuke; Morimura, Ryo; Kuriu, Yoshiaki; Ikoma, Hisashi; et al.
Abstract: The aim of the present study was to evaluate subcarinal lymph node dissection in transmediastinal radical esophagectomy and subcarinal lymph node metastasis in patients with esophageal cancer and to identify predictive factors for subcarinal lymph node metastasis. Three hundred and twenty-three patients with primary esophageal cancer who underwent transmediastinal or transthoracic esophagectomy with radical two- or three-field lymph node dissection were retrospectively investigated. The clinicopathological characteristics of patients with subcarinal lymph node metastasis were analyzed in detail. The median number of dissected subcarinal lymph nodes in transmediastinal and transthoracic esophagectomy groups was 6 and 7, respectively, and there was no significant difference between the two groups (p = 0.12). Of all patients, 26 (8.0%) were pathologically diagnosed as positive for subcarinal lymph node metastasis. By univariate analysis, subcarinal lymph node metastasis was found in larger (≥ 30 mm) and deeper (T3/T4a) primary lesions (p = 0.02 and 0.02, respectively), but it was not found in patients (n = 49) with the primary lesion located in the upper thoracic esophagus. Subcarinal lymph nodes can be dissected in transmediastinal esophagectomy, almost equivalent to transthoracic esophagectomy. The tumor size, depth, and location may be predictive factors for subcarinal lymph node metastasis.